Characterization, calibration and application in radiotherapy of a dosimetric system based on detectors AT2OR3: C - Márquez Pachas, José Fernando (2022)
In radiotherapy, it is essential to have an alternative dosimetric system to identify possible errors at some stage of the process. The optically stimulated luminescence (OSL) technology represents a great advance in the detection of radiation in different areas, one of them being in the area of clinical dosimetry. Objective: To implement an alternative dosimetric system, based on OSL technology of carbon-doped aluminum oxide crystals.  Material and methods: Al2or3:C detectors called "nanodot", MicroStar reader, ionization chambers (Standard Imaging and PTW Freiburg), electrometers (PTW-Freiburg and MNCNP) and other accessories.  Results: The dosimetric - algorithmic procedure, developed for the calculation of the adsorbed dose in the tumor volume, reproduces the dose values with uncertainties less than 2% for a confidence level of 95% and with relative differences less than 5% compared to the values of the absorbed doses prescribed and / or foreseen in radiotherapy treatments.  Conclusions: The nanodot detectors  represent a viable alternative for the verification of the absorbed dose in the patient during radiotherapeutic practice for the verification of the prescribed dose and imparted by in vivo dosimetry. Its quality to preserve the information, as a physical witness of the procedure, contributes to security in the treatments.